Optimal Fiscal Policy and the Environment - Ligthart, Jenny (IMF Working Papers; Working Paper, 1998)
The paper studies the setting of optimal fiscal policy in a second-best world with environmental externalities. The optimal second-best pollution tax is shown to lie below the first-best Pigovian tax, particularly if substitution between labor and polluting intermediate inputs is easy, the labor supply curve is more elastic, and preexisting taxes are large. The optimal level of public abatement is derived from the modified Samuelson rule and is larger if society cares more for the environment, public funds are inexpensive, and public abatement is relatively productive. The analysis also shows that the Samuelson rule should be revised if allowance is made for nonseparabilities in preferences.